2007
DOI: 10.1177/0146167207310024
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Interference: Adult Attachment and Emotional Processing Biases

Abstract: The present study investigated attachment-related differences in emotional processing biases. Consistent with the proposal that avoidant individuals limit attention to potentially distressing information, attachment avoidance was associated with reductions in emotional Stroop (ES) interference for attachment-related words (e.g., intimate, loss). These biases were strongest among individuals who were currently in a romantic relationship, suggesting that being in a close relationship may activate avoidant defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
3
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 57 publications
8
108
3
15
Order By: Relevance
“…This may have deleterious effects Another interesting result on attachment avoidance is that the regulatory strategies of avoidant individuals were found to be specifically oriented towards inhibiting cues of rejection and distress. This, however, does not fit well with other research showing that deactivating strategies limit the processing of any emotional material, both positive and negative, that makes salient attachment needs (Edelstein, 2006;Edelstein & Gillath, 2008;Niedenthal, Brauer, Robin, & Innes-Ker, 2002). Yet, this divergence in results may partially be explained by the methodological differences between our study and previous studies examining emotional processing biases in the context of attachment.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…This may have deleterious effects Another interesting result on attachment avoidance is that the regulatory strategies of avoidant individuals were found to be specifically oriented towards inhibiting cues of rejection and distress. This, however, does not fit well with other research showing that deactivating strategies limit the processing of any emotional material, both positive and negative, that makes salient attachment needs (Edelstein, 2006;Edelstein & Gillath, 2008;Niedenthal, Brauer, Robin, & Innes-Ker, 2002). Yet, this divergence in results may partially be explained by the methodological differences between our study and previous studies examining emotional processing biases in the context of attachment.…”
Section: Discussioncontrasting
confidence: 91%
“…Such automatic processes were measured in a recent study in which an emotional Stroop task was used to investigate cognitive interference of attachment-related threat words (Edelstein & Gillath, 2008). Results showed that attachment avoidance was associated with a reduced Stroop interference effect for negative emotional words, which was interpreted in terms of avoidant individuals' tendency to inhibit attentional processing of potentially threatening information.…”
Section: Inhibitory Processing Of Attachment-related Affectmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to strong feelings of distrust of others, these individuals actively avoid and dismiss thoughts and feelings that could lead to closeness and interdependence. The act of suppressing potentially threatening information and keeping it out of awareness requires the allocation and maintenance of cognitive resources (Ochsner & Gross, 2005), which can be disrupted and depleted under conditions of elevated cognitive load or intense emotion (Caldwell, Krug, Carter, & Minzenberg, in press;Edelstein & Gillath, 2008;Mikulincer, Dolev, & Shaver, 2004), resulting in the breakdown of attentional control and diminished capacity for self-reflection and mindful awareness. can be viewed as an attempt to keep the fleeting relationship alive and guard against perceived threats of abandonment and loss.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adult attachment insecurity is related to poor attentional control, whereas attachment-related security is associated with more open and flexible attention (Edelstein & Gillath, 2008;Fraley & Shaver, 1997;Gillath, Bunge, Shaver, Wendelken, & Mikulincer, 2005). We posit that the defensive maneuvering inherent in hyperactivating (anxious) and deactivating (avoidant) attachment strategies deplete attentional resources, leaving people with less capacity for mindful awareness.…”
Section: Introductionmentioning
confidence: 90%